Cuttings-liquid frictional pressure loss model for horizontal narrow annular flow with rotating drillpipe - Ofei, T.N. (Institute of Physics Publishing, 2015)
During oil and gas drilling operations, frictional pressure loss is experienced as the drilling fluid transports the drilled cuttings from the bottom-hole, through the annulus, to the surface. Estimation of these pressure losses is critical when designing the drilling hydraulic program. Two-phase frictional pressure loss in the annulus is very difficult to predict, and even more complex when there is drillpipe rotation. Accurate prediction will ensure that the correct equivalent circulating density (ECD) is applied in the wellbore to prevent formation fracture, especially in formations with narrow window between the pore pressure and fracture gradient. Few researchers have attempted to propose cuttings-liquid frictional pressure loss models, nevertheless, these models fail when they are applied to narrow wellbores such as in casing- while-drilling and slimhole applications. This study proposes improved cuttings-liquid frictional pressure loss models for narrow horizontal annuli with drillpipe rotation using Dimensional Analysis. Both Newtonian and non-Newtonian fluids were considered. The proposed model constants were fitted by generated data from a full-scale simulation study using ANSYS-CFX. The models showed improvement over existing cuttings-liquid pressure loss correlations in literature. Â© Published under licence by IOP Publishing Ltd.